Effectiveness of Brackish Water Desalination Using Reverse Osmosis System for Industrial Water Treatment at PLTU PT Bintan Alumina Indonesia - Simanjuntak, Yosia Putra (Politeknik Negeri Semarang, 2023)
Abstract- Demineralized water is water that does not contain high minerals or chemicals, and is used as feed to the boiler to produce steam. Demineralized water is very important in the PLTU (Steam Power Plant) industry because steam is produced through the process of changing the phase of water to steam. Natural water tends to be corrosive because it contains minerals such as high calcium and magnesium, which can cause scale in the boiler and reduce energy efficiency. Therefore, these minerals must be removed from the water so that they can be used as boiler feed. To produce demin water, PT. BAI uses a Water Treatment Plant (WTP) system which consists of several stages, such as a clarifier, a three-layer filter, an automatic cleaning filter, ultra-filtration and reverse osmosis. After going through these processes, demin water is stored in tanks and then flowed to the main plant. There are several factors that can interfere with the demin water production process at PT. BAI, including changes in water quality, problems with WTP equipment, and disturbances in the water distribution system. This study aims to maintain the reliability and efficiency of the demin water production process, by carrying out routine maintenance on equipment, monitoring water quality by checking conductivity, pH levels, and produced water. Then from the data obtained it can be seen that the efficiency of demin water has met the operating standards and procedures set by PT.BAI, namely desalination levels above 90%. The division must also always be ready to deal with problems that occur and take preventive actions to prevent disruption to the production process.